PENGARUH KETERLIBATAN PEMAKAI, PELATIHAN, UKURAN ORGANISASI DAN KEAHLIAN PEMAKAI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Arya Damana, Agus Wahyu; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2016)
Accounting information systems is very important in the institution to support the smooth performance of the institution, an institution is required to assess the performance of good financial statements and complete, therefore it is necessary also an accounting information system supported by computerized information technology. This study aimed to determine whether user involvement, training, organizational size, and user expertise to affect the performance of accounting information system on Credit Institutions village in Klungkung regency. The sample used in this study were 51 obtained by purposive sampling technique, namely the determination of the sample based on the characteristics and suitability of certain criteria. The data analysis technique used in this research is multiple linear regression analysis, which is preceded by the classical assumption, which is processed with SPSS for Windows version 16.0. Based on the results of the analysis of user involvement, training, organizational size, and user expertise positive effect on the performance of the accounting information system with a significance value less than 0.05
Keywords: User involvement, Training, Organization Size, and Performance Accounting Information Systems